Norepinephrine is a negative regulator of the adult periventricular neural stem cell niche. (25th June 2020) - Weselek, Grit; Keiner, Silke; Fauser, Mareike; Wagenführ, Lisa; Müller, Julia; Kaltschmidt, Barbara; Brandt, Moritz D.; Gerlach, Manfred; Redecker, Christoph; Hermann, Andreas; Storch, Alexander
Abstract: The limited proliferative capacity of neuroprogenitor cells (NPCs) within the periventricular germinal niches (PGNs) located caudal of the subventricular zone (SVZ) of the lateral ventricles together with their high proliferation capacity after isolation strongly implicates cell‐extrinsic humoral factors restricting NPC proliferation in the hypothalamic and midbrain PGNs. We comparatively examined the effects of norepinephrine (NE) as an endogenous candidate regulator of PGN neurogenesis in the SVZ as well as the periventricular hypothalamus and the periaqueductal midbrain. Histological and neurochemical analyses revealed that the pattern of NE innervation of the adult PGNs is inversely associated with their in vivo NPC proliferation capacity with low NE levels coupled to high NPC proliferation in the SVZ but high NE levels coupled to low NPC proliferation in hypothalamic and midbrain PGNs. Intraventricular infusion of NE decreased NPC proliferation and neurogenesis in the SVZ‐olfactory bulb system, while pharmacological NE inhibition increased NPC proliferation and early neurogenesis events in the caudal PGNs. Neurotoxic ablation of NE neurons using the Dsp4‐fluoxetine protocol confirmed its inhibitory effects on NPC proliferation. Contrarily, NE depletion largely impairs NPC proliferation within the hippocampus in the same animals. Our data indicate that norepinephrine has opposite effects on the two fundamental neurogenic niches of the adult brain with norepinephrine being a negative regulator of adult periventricular neurogenesis. This knowledge might ultimately lead to new therapeutic approaches to influence neurogenesis in hypothalamus‐related metabolic diseases or to stimulate endogenous regenerative potential in neurodegenerative processes such as Parkinson's disease. Abstract : Intracerebroventricular (i.c.v.) infusion of norepinephrine (NE) decreases neuroprogenitor cell (NPC) proliferation (arrows) within the subventricular zone (SVZ) of the lateral ventricles (LV) and neurogenesis in the SVZ‐olfactory bulb system without changing cells type composition of the SVZ. In contrast, pharmacological NE inhibition increases the proliferation of various NPC types and early neurogenesis events in the caudal periventricular germinal niche (PGN) of the third ventricle (3V). Neurotoxic ablation of norepinephrine neurons within the Locus coeruleus (LC) using Dsp4 confirms the inhibitory effects of NE on NPC proliferation within the 3V‐PGN. This effect is reversed by NE i.c.v. infusion. Contrarily, NE depletion largely impairs NPC proliferation within the hippocampus in the same animals. Our data indicate that NE has opposite effects on the two fundamental neurogenic niches of the adult brain with norepinephrine being a negative regulator of adult periventricular neurogenesis.